Correlation between cystometric volumes, ATP release, and pH in women with overactive bladder versus controls12. Issue 7 (5th November 2012) - Cheng, Ying; Mansfield, Kylie J.; Allen, Wendy; Millard, Richard J.; Burcher, Elizabeth; Moore, Kate H.
Abstract Aims In the bladder, ATP is an important signaling molecule, which is released by bladder stretch and acid. We hypothesized that ATP might play a unique role in patients with OAB, characterized by low bladder volumes at first desire to void (FDV) and maximal cystometric capacity (MCC) and symptoms of frequency/urgency [mild bladder pain syndrome (BPS)]. Our aim was to investigate the correlation between ATP release and urodynamic parameters, as well as urine pH, in OAB patients. Methods Routine cystometry was performed in a consecutive series of 249 women. The voided urodynamic fluid (VUF) was stored at −20°C and ATP measured using bioluminescence. Catheter urine was collected for pH measurement. Correlations between two factors were tested by linear regression analysis. Results Subjects with urinary tract infection, voiding dysfunction, and detrusor overactivity (DO) were excluded. For OAB patients (n = 25), there was an inverse correlation between ATP concentration in VUF and FDV (r2 = 0.25; P = 0.01) but not MCC. This was not seen in controls (n = 69). In OAB, but not controls, there was a significant reverse correlation (r2 = 0.16; P = 0.047) between ATP in VUF and urine pH. Urine pH was not significantly correlated with MCC in either group. Conclusions In OAB patients, ATP is an important factor for initial perception of need to urinate (as indicated by FDV). This is similar to our previous findings in patients with DO, suggesting that ATP may mediate initial afferent sensation in patients with bladder dysfunctions characterized by urgency. ATP release was also strongly affected by urine pH, in patients with OAB (at FDV). Neurourol. Urodynam. 32: 969–973, 2013. © 2012 Wiley Periodicals, Inc.